2009
DOI: 10.1103/physrevd.79.044028
|View full text |Cite
|
Sign up to set email alerts
|

Detecting chameleons: The astronomical polarization produced by chameleonlike scalar fields

Abstract: We show that a coupling between chameleon-like scalar fields and photons induces linear and circular polarization in the light from astrophysical sources. In this context chameleon-like scalar fields includes those of the Olive-Pospelov (OP) model, which describes a varying fine structure constant. We determine the form of this polarization numerically and give analytic expressions in two useful limits. By comparing the predicted signal with current observations we are able to improve the constraints on the ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 111 publications
5
118
0
Order By: Relevance
“…For example, observations of circularly-polarized starlight in the wavelength range 1 − 10 3Å could be a strong indication of mixing between chameleons and photons [876]. A difference in the ratio of the electron to proton mass between laboratories on Earth and in space can be measured and would indicate the presence of a chameleon-like scalar particle [898].…”
Section: Galaxies In the Nearby Universementioning
confidence: 99%
See 2 more Smart Citations
“…For example, observations of circularly-polarized starlight in the wavelength range 1 − 10 3Å could be a strong indication of mixing between chameleons and photons [876]. A difference in the ratio of the electron to proton mass between laboratories on Earth and in space can be measured and would indicate the presence of a chameleon-like scalar particle [898].…”
Section: Galaxies In the Nearby Universementioning
confidence: 99%
“…A difference in the ratio of the electron to proton mass between laboratories on Earth and in space can be measured and would indicate the presence of a chameleon-like scalar particle [898]. In [876,898], it was shown that the scatter in the luminosity of astrophysical objects can be used to search for chameleons, particularly through observing active galactic nuclei.…”
Section: Galaxies In the Nearby Universementioning
confidence: 99%
See 1 more Smart Citation
“…Early examples of dark energy in the form of a scalar field with a self-interaction potential can be found in a review by Peebles & Ratra (2003). To explain the nature of dark energy, many sophisticated models have been suggested (see, e.g., Caldwell et al 1998), and among them the scalar fields that are ultralight in the cosmic vacuum but that possess a high mass locally when they are coupled to ordinary matter by the so-called chameleon mechanism A&A 524, A32 (2010) (Khoury & Weltman 2004a,b;Brax et al 2004;Avelino 2008;Burrage et al 2009;Davis et al 2009;Brax 2009;Upadhye et al 2010;Brax & Zioutas 2010). A subclass of such models considered by Olive & Pospelov (2008) predicts that fundamental physical quantities, such as elementary particle masses and lowenergy coupling constants, may also depend on the local matter density.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper deals with one such astronomical test based on spectral observations of molecular clouds in the Milky Way disk. Additional tests employing polarization of the light from the stars and a modification of the Sunyaev-Zel'dovich effect in the cosmic microwave background due to a coupling between a chameleon-like scalar field and photons are described, respectively, in Burrage et al (2009) and Davis et al (2009).…”
Section: Introductionmentioning
confidence: 99%